Tanggung Jawab Pemerintah Dalam Perencanaan Pembangunan Kecamatan Yang Partisipatif - Falantina Theresia Naryemin; Jantje Tjiptabudy; Erick Stenly Holle (Faculty of Law Pattimura University, 2022)
Introduction: The administration of government through Law Number 23 of 2014 concerning Regional Government is one of the means in realizing a democratic government that involves all the potential of the community to participate in thinking and managing regional government. The purpose of this study was to determine how the form of government responsibility in participatory development planning and to find out what factors influence community participation in development planning.Purposes of the Research: The purpose of this research was to determine how the form of government responsibility in participatory development planning and to find out what factors influence community participation in development planning.Methods of the Research: The research method used is a normative legal research method. The problem approach used is the statutory approach, the conceptual approach. The legal materials used are primary legal materials and secondary legal materials. Procedures and Collection of Legal Materials using the method of inventorying laws and regulations and Processing and Analysis of legal materials using data analysis techniques with deductive logic.Results of the Research: Based on the results of the study, it can be concluded that the Kudamati sub-district government has made efforts and roles, such as inviting the community to participate in various village activities with the aim of increasing community participation in development in accordance with the content, objectives, and intentions of each development program that wants to be implemented in accordance with with their responsibilities and the community as supporting factors, it is stated that it is not good if it is seen from the low participation of the Kudamati Village community.